Antioxidant and anticancer activities from leaf extracts of four Combretum species from Northern Thailand - Wimaluk Nopsiri (2018)
Four Combretum species (Combretaceae) from northern Thailand (Combretum deciduum, Combretum griffithii, Combretum latifolium and Combretum quadrangulare) were tested for antioxidant and anticancer activities. Antioxidant activities were assessed by ABTS and DPPH radical scavenging capacity methods. Anticancer activity was tested against three cancerous human cell lines (KB, MCF7 and NCI-H187). All methanolic leaf extracts showed antioxidant activities with the ABTS and DPPH methods. The methanolic leaf extracts of C. deciduum inhibited KB-oral cavity and MCF7-breast cancer cell lines, C. latifolium inhibited MCF7-breast cancer cell line and C. quadrangulare inhibited KB-oral cavity and NCI-H187-small cell lung cancer cell lines. However, the methanolic leaf extracts of C. griffithii were inactive against all three cell lines. All methanolic leaf extracts exhibited non-cytotoxicity to Vero cell lines.